Theoretical foundations of the formation of communicative competence among students in the process of teaching the Russian language and culture of speech - Zinin, Yevgeniy Olegovich; Obidova, Shahnoza (Science and Education, 2023)
The article discusses the theoretical foundations of the formation of communicative competence among students-bunning students in the process of teaching the Russian language and speech culture.